2018
DOI: 10.1097/prs.0000000000004173
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Efficacy and Costs of Four Facial Fillers in Human Immunodeficiency Virus–Associated Lipodystrophy: A Clinical Trial

Abstract: Surgical treatment of human immunodeficiency virus-associated facial lipoatrophy using dermal fillers is a safe and effective procedure that improves the aesthetic appearance and the quality of life of patients. Permanent fillers and autologous fat achieve the most consistent results over time, with lipofilling being the most cost-effective procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Autologous fat transplantation is considered an ideal method for soft tissue surgery and repair in plastic and reconstructive surgery due to its bioavailability and biocompatibility [ 1 ]. Fat grafting for reconstruction or aesthetic surgery usually requires multiple transplantations to achieve the treatment goals due to its unpredictable absorption rates [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous fat transplantation is considered an ideal method for soft tissue surgery and repair in plastic and reconstructive surgery due to its bioavailability and biocompatibility [ 1 ]. Fat grafting for reconstruction or aesthetic surgery usually requires multiple transplantations to achieve the treatment goals due to its unpredictable absorption rates [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A summary of studies included concerning HIV-FLA is reported in Table 2. [16][17][18][19] Injections were performed subdermally or supraperiostally with needles or cannulas. Variables assessed included determining improvement in all treated patients, evaluated according to Fontdevila's FLA grade or the global assessment improvement scale (GAIS), without any adverse events.…”
Section: Hiv-associated Facial Lipoatrophymentioning
confidence: 99%
“…Human immunodeficiency virus treated with highly active antiretroviral therapy can result in facial lipoatrophy in these patients. 42 The FDA has approved use of calcium hydroxylapatite and poly-L-lactic acid for filling volume loss in the contours of the cheeks, temples, and orbits. 42 There are new emerging uses for facial fillers currently being adopted into practice.…”
Section: Injectable Fillersmentioning
confidence: 99%
“…42 The FDA has approved use of calcium hydroxylapatite and poly-L-lactic acid for filling volume loss in the contours of the cheeks, temples, and orbits. 42 There are new emerging uses for facial fillers currently being adopted into practice. Filler use in the temporal areas can correct for loss of volume, preventing a gaunt facial appearance.…”
Section: Injectable Fillersmentioning
confidence: 99%